THE DEVELOPMENT OF SCIENCE PRACTICUM GUIDENCE FOR 9th GRADE STUDENTS’ ON STATIC ELECTRICITY SUBJECT - Novita, Yolla; Putri, Rahmah Evita (Universe, 2025)
Learning is a process of interaction between educators and students as well as learning resources in a learning environment. Interaction will work well if the teacher can explain learning correctly, is easy to understand and uses the right learning media. Teaching materials used by students during the learning process are literacy books and textbooks. There is no learning media in the form of a practicum guidebook so that it results in a directed and safe practicum activity not being carried out. Based on these problems, it is necessary to develop instructional media in the form of practicum guides as science teaching materials for class IX in junior high school. The type of research used is Research and Development (R&D) using a 4-D model which is only carried out until the development stage. The location of the research was at SMPN 14 Padang and FMIPA UNP. At the development stage, 3 expert validators, 3 science teachers and 30 class IX students of SMPN 14 Padang carried out the validation of the practicum guide. The results of the study show that the static electricity practicum guide is valid and practical.